Location-based challenges for playful neighbourhood exploration. Issue 2 (25th January 2022) - Slingerland, Geertje; Fonseca, Xavier; Lukosch, Stephan; Brazier, Frances
ABSTRACT: Location-based activities can challenge citizens to explore their neighbourhood in new playful ways. This paper presents a classification of such playful activities based on the literature and experience gained (1) in co-creation sessions and (2) gameplay for neighbourhood exploration with citizens in the Hague. The location-based game designed for this purpose encouraged neighbourhood exploration and social interaction that went beyond the everyday normal. Results showed that citizens are specifically interested in activities that allow them to discover new information about, and places in, their neighbourhood when these are related to their own life. The results of this paper provide new knowledge on game design to inform designers on which type of interactions and activities foster neighbourhood exploration and social interaction.